2012
DOI: 10.4093/dmj.2012.36.6.399
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Type 2 Diabetes Mellitus

Abstract: Cigarette smoking is a well-known risk factor in many diseases, including various kinds of cancer and cardiovascular disease. Many studies have also reported the unfavorable effects of smoking for diabetes mellitus. Smoking increases the risk of developing diabetes, and aggravates the micro- and macro-vascular complications of diabetes mellitus. Smoking is associated with insulin resistance, inflammation and dyslipidemia, but the exact mechanisms through which smoking influences diabetes mellitus are not clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
138
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(165 citation statements)
references
References 38 publications
12
138
2
3
Order By: Relevance
“…For example, among some cultures and ethnic groups the obesity is considered favorable and represent prosperity, in some smoking represent social status or class etc. At physiological and biochemical levels, the literature review in the area reveals that even though smoking can cause a decrease in the body weight, is associated with central obesity and oxidative stress both of which could lead to insulin resistance through several complex metabolic mechanisms [4][5][6]. The direct effect of smoking on diabetes could be associated with inflammatory and oxidative stress along with damaging impact on the beta cells of pancreas [5].…”
Section: To the Editormentioning
confidence: 99%
See 3 more Smart Citations
“…For example, among some cultures and ethnic groups the obesity is considered favorable and represent prosperity, in some smoking represent social status or class etc. At physiological and biochemical levels, the literature review in the area reveals that even though smoking can cause a decrease in the body weight, is associated with central obesity and oxidative stress both of which could lead to insulin resistance through several complex metabolic mechanisms [4][5][6]. The direct effect of smoking on diabetes could be associated with inflammatory and oxidative stress along with damaging impact on the beta cells of pancreas [5].…”
Section: To the Editormentioning
confidence: 99%
“…At physiological and biochemical levels, the literature review in the area reveals that even though smoking can cause a decrease in the body weight, is associated with central obesity and oxidative stress both of which could lead to insulin resistance through several complex metabolic mechanisms [4][5][6]. The direct effect of smoking on diabetes could be associated with inflammatory and oxidative stress along with damaging impact on the beta cells of pancreas [5]. Since, smoking can lead to the central obesity [4], increased abdominal and/or body fat leads to the higher levels of inflammatory substances such as cytokines, TNF-α, IL-6, etc.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Smoking has been considered to be associated with diabetes and to predispose to diabetes related complications across studies, 25,[33][34][35] while its association with dyslipidemia and increased blood pressure has been inconclusive in literature [36][37][38][39][40] with a large scale population based, long-term follow up study reporting smoking to be an independent risk factor for CVD with clinically little effect on blood pressure and cholesterol, especially in those above 46years of age. 35 But in our study we found no significant association of smoking status with hypertension, diabetes and dyslipidemia.…”
mentioning
confidence: 99%